2007
DOI: 10.1128/jb.01382-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of the β1 Subunit in the Function and Stability of the 20S Proteasome in the Hyperthermophilic ArchaeonPyrococcus furiosus

Abstract: The hyperthermophilic archaeon Pyrococcus furiosus genome encodes three proteasome component proteins: one ␣ protein (PF1571) and two ␤ proteins (␤1-PF1404 and ␤2-PF0159), as well as an ATPase (PF0115), referred to as proteasome-activating nucleotidase. Transcriptional analysis of the P. furiosus dynamic heat shock response (shift from 90 to 105°C) showed that the ␤1 gene was up-regulated over twofold within 5 minutes, suggesting a specific role during thermal stress. Consistent with transcriptional data, two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…HsC2/HsPROS30 30.2 Kania et al (1996Kania et al ( , 2005 a7 C1/ Prs1 HsC8 28.4 Bose et al (2004), Gerards et al (1997), Gerards et al (1998) and Shu et al (2003) b1 Pre3 HsDelta/Y 25.3 (21.9) Chung et al (2000), Lequeu et al (2005), Madding et al (2007) b1i -Lmp2 23.2 (20.9) Dissemond et al (2003), , and Krause et al (2006) b2 Pup1 Z 30.0 (24.5) Schweisguth (1999), Ramos et al (2004) and Baldisserotto et al (2007) b2i -Mecl1 28.9 (23.8) Scheffler et al (2008) and Eleuteri et al (1997) b3 Pup3…”
Section: The 20s Proteasomementioning
confidence: 95%
“…HsC2/HsPROS30 30.2 Kania et al (1996Kania et al ( , 2005 a7 C1/ Prs1 HsC8 28.4 Bose et al (2004), Gerards et al (1997), Gerards et al (1998) and Shu et al (2003) b1 Pre3 HsDelta/Y 25.3 (21.9) Chung et al (2000), Lequeu et al (2005), Madding et al (2007) b1i -Lmp2 23.2 (20.9) Dissemond et al (2003), , and Krause et al (2006) b2 Pup1 Z 30.0 (24.5) Schweisguth (1999), Ramos et al (2004) and Baldisserotto et al (2007) b2i -Mecl1 28.9 (23.8) Scheffler et al (2008) and Eleuteri et al (1997) b3 Pup3…”
Section: The 20s Proteasomementioning
confidence: 95%
“…Pyrococcus furiosus also encodes three CP subunits (α, β1 and β2). Of these, β1 subunit transcript levels are upregulated during heat shock, and CPs with the greatest ratio of β1/β2 are the most thermostable 113 . Thus, P. furiosus might incorporate β1 into CPs to enhance proteasome function during thermal stress.…”
Section: Proteasome Systems In a Cellular Contextmentioning
confidence: 99%
“… These results indicate that the β1 protein in the P. furiosus 20S proteasome plays a thermostabilizing role at supraoptimal temperatures and suggests that subunit composition can be a factor in proteasome function during thermal stress when polypeptide turnover is essential to cell survival (Madding et al, 2007).…”
Section: (3) Exopolysaccharide/biofilm Formation By T Maritimamentioning
confidence: 83%
“…(5) Role of 20S proteasome β protein in the hyperthermophilic archaeon Pyrococcus furiosus during thermal stress  Transcriptional analysis of P. furiosus subjected to heat shock (shift from 90 to 105°C) showed that expression of the β2 gene (PF0159) in the archaeal proteasome was affected differently than the β1 gene (PF1404), suggesting different roles in thermal stress response for the subunits (Madding et al, 2007).…”
Section: (3) Exopolysaccharide/biofilm Formation By T Maritimamentioning
confidence: 99%